DDIS-14. MODIFIED CARBAZOLES DESTABILIZE MICROTUBULES AND KILL GLIOBLASTOMA MULTIFORM CELLS. (5th November 2018) - Stella, Nephi; Diaz, Philippe; Horne, Eric; Xu, Cong; Hamel, Ernest; Wagenbach, Mike; Petrov, Ravil; Hass, Brian; Parvinder, Hothi; Wordeman, Linda; Gussio, Rick
Abstract: Small molecules that target microtubules (MTs) represent promising therapeutics to treat certain types of cancer, including glioblastoma multiform (GBM). We synthesized modified carbazoles and evaluated their antitumor activity in GBM cells in culture. Modified carbazoles with an ethyl moiety linked to the nitrogen of the carbazole and a carbonyl moiety linked to distinct biaromatic rings exhibited remarkably different killing activities in human GBM cell lines and patient-derived GBM cells, with IC50 values from 67 to > 10, 000 nM. Measures of the activity of modified carbazoles with tubulin and microtubules coupled to molecular docking studies show that these compounds bind to the colchicine site of tubulin in a unique low interaction space that inhibits tubulin assembly. The modified carbazoles reported here represent novel chemical tools to better understand how small molecules disrupt MT functions and kill devastating cancers such as GBM.